The effectiveness of writing techniques in improving students’ writing ability with different self-esteem - Ida Yulianawati; Mursid Saleh; Januarius Mujiyanto; Djoko Sutopo (Studies in English Language and Education, 2022)
Identifying appropriate writing techniques to help students with different self-esteem improve their writing ability needs to be considered by educators. This study attempted to examine the effectiveness of two writing techniques, Reflective Learning Portfolio (RLP) and Dialogue Journal Writing (DJW) in improving the writing ability of undergraduate students with different self-esteem. A quasi-experimental design was employed in this study. The participants of the study were 62 undergraduate students from a private university in West Java, Indonesia, which were divided into two groups that received different treatments, RLP and DJW techniques. A set of questionnaires to measure students’ self-esteem and writing tests were utilized to collect the data. Data from questionnaires were analyzed by using Likert Scales. Data from pre-test and post-test, to know the effectiveness of RLP and DJW was administered by using a paired t-test. The finding revealed that the writing performance in RLP class was significantly better than in DJW class. In other words, RLP is more effective in teaching writing to students with different self-esteem. The use of explicit teaching, peer feedback, and teacher feedback in RLP class could have caused the RLP technique to be more effective in improving the students’ writing ability compared to the DJW technique.